FLEXIBLY SHAPED SPATIAL SCAN STATISTIC FOR MAPPING INDONESIAN STUNTING INCIDENTS - Fauziyah, Meirinda; Asnita, Asnita; Hayati, Memi Nor; Hadistii, Zahrah Dhafiinia (Universitas Islam Negeri Imam Bonjol Padang, 2023)
The early stages of toddler growth are vulnerable to the environment around them. The growth of toddlers can be influenced by the nutritional intake they receive. One of the poor nutritional statuses that often occurs in toddlers is stunting. Toddlers who experience stunting are at risk of decreasing intellectual abilities, productivity, and increasing the risk of degenerative diseases in the future. The research variables used are the percentage of the poor population and the prevalence of stunting in Indonesia in 2021 using the Flexibly Shaped Spatial Scan Statistic (FSSS) analysis method. The results of the research show that there are areas in hotspot 1 which are areas potentially prone to stunting prevalence. Provinces that are potentially vulnerable are Aceh, North Sumatra, West Sumatra, Riau, Jambi, Bengkulu.